"Out there in that cabin in the middle of nowhere in Montana": Narrating the Geographical and Mental Deviance of the Unabomber - Robert Winkler (Journal of the Austrian Association for American Studies)
In 1996, the mathematician-turned-terrorist Theodore J. Kaczynski, nicknamed the Unabomber, was arrested in his self-built cabin in the woods of Montana after having terrorized the nation for over 20 years. He had modeled his cabin after Henry David Thoreau's idealized Walden cabin. This article argues that the Unabomber's cabin in Montana, often considered a so-called flyover state, serves as the pivotal point for his geographical marginalization in the media coverage of the case. Its location in what is discursively constructed as a 'wilderness' makes it impossible to perceive his cabin through the perspective of the pastoral ideal – this imagined middle ground between nature and culture. The over-determination of this material form in its location apparently off the grid furthermore enables the othering and medicalization of Theodore J. Kaczynski. This article demonstrates that the media coverage of the Unabomber case displays these three tendencies which come together in the nexus cabinsanity, i.e., the conflation of pseudo-geographical, cultural, and medical discourses. Projecting cabinsanity, in turn, enables the dismissal of the Unabomber's critique of technologized society as delineated in his manifesto.